Powder assembly & alloying to CNT/Al–Cu–Mg composites with trimodal grain structure and strength-ductility synergy. (15th November 2021) - Fu, Xiaowen; Tan, Zhanqiu; Ma, Ziqi; Li, Zan; Fan, Genlian; Xiong, Ding-Bang; Li, Zhiqiang
Abstract: A novel strategy of powder assembly & alloying was used to achieve trimodal grain structure in carbon nanotubes (CNTs) reinforced aluminum matrix composites. The soft pure Al and hard 2024Al powders were firstly ball milled with CNTs for CNT/Al and CNT/2024Al flakes with different thicknesses, then were assembled with coarse-grained pure Al powders. Under the confinement of CNTs, these three building blocks evolved into ultrafine grains (UFG) smaller than 500 nm, fine grains (FG) between 500 nm and 2 μm and coarse grains (CG) about 9.8 μm, respectively, while the Al–Cu–Mg matrix achieved by the diffusion of Cu and Mg powders and elemental alloying with Al. Such a UFG-FG-CG trimodal grain structure contributed to superior strength-ductility synergy, as the 1.5 wt% CNT/Al–Cu–Mg composites exhibited tensile strength of 723 ± 6 MPa and elongation of 6.7 ± 0.6%. Therefore, powder assembly & alloying was proved an effective way to design and fabricate heterogeneous structured metal matrix nanocomposites.